1927
DOI: 10.1113/jphysiol.1927.sp002375
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the contractility of lacteals

Abstract: THE appearances presented by the lacteals on microscopic examination of the mesentery in the guinea-pig and rat have been described in a. previous communication(i). The rhythmical activities of these vessels have been examined, from the point of view of their initiation and control, both by means of nerve stimulation and drug action. The appearances and reactions presented by the lacteals and lymph glands of other species are also described.It was possible with the microdissection apparatus to inject minute qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

1931
1931
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 6 publications
(7 reference statements)
1
66
0
Order By: Relevance
“…Movement of lymph depends upon forces outside the lymphatic system'. This conviction seems curious bearing in mind that Hewson (1774) and Florey (1927) had already observed that lymphatic ducts were rhythmically contractile. However, even today, the idea that a small pressure gradient from lymph capillary to central veins (vis a tergo) and the massaging effects of arterial pulsation and muscular contractions are primarily responsible for lymph propulsion is so intuitively appealing that it has been a difficult one (in the words of Staub & Albertine, 1985) 'to extirpate from the literature'.…”
Section: Discussionmentioning
confidence: 96%
“…Movement of lymph depends upon forces outside the lymphatic system'. This conviction seems curious bearing in mind that Hewson (1774) and Florey (1927) had already observed that lymphatic ducts were rhythmically contractile. However, even today, the idea that a small pressure gradient from lymph capillary to central veins (vis a tergo) and the massaging effects of arterial pulsation and muscular contractions are primarily responsible for lymph propulsion is so intuitively appealing that it has been a difficult one (in the words of Staub & Albertine, 1985) 'to extirpate from the literature'.…”
Section: Discussionmentioning
confidence: 96%
“…Rhythmic contractions have been observed in many varieties of lymph vessels in vivo (Hewson, 1774;Florey, 1927;Smith, 1949;Kinmonth & Taylor, 1956). Hall, Morris & Wooley (1965) established lymphatic fistulae in conscious sheep and recorded pulsatile pressures ranging from 1 to 25 mmHg at frequencies from 1 to 30/min.…”
Section: Discussionmentioning
confidence: 99%
“…Many lymphatic and blood vessels exhibit vasomotion, a rhythmic constriction -dilation cycle of these vessels (Florey, 1927;Johnson, 1980). This mechanism is responsible for both the propulsion of lymph (each phasic constriction pumping lymph forward through unidirectional valves within lymphatic vessels; Mislin, 1983;Johnston & Elias, 1987;McHale, 1990), and for modulating the local vascular resistance and blood flow (see Haddock et al, 2002).…”
Section: Introductionmentioning
confidence: 99%